Book Reviews - Saucedo Torres, Vincente; Russo, Maria Teresa; Fernández Labastida, Francisco; Ducay, Antonio; Russo, Francesco; Brock, Stephen L. (Acta Philosophica, 2002)
Julia Annas, Platonic Ethics, Old and New, [Cornell Studies in Classical Philology, 57], Cornell University Press, Ithaca & London 1999, The Towsend Lectures I, pp. 196. (V. Saucedo Torres) Henri Bergson, Il pensiero e il movente. Saggi e conferenze, a cura di G. Perrotti, Leo S. Olschki, Firenze 2001, pp. 171. (M.T. Russo) Lourdes Flamarique, Schleiermacher. La filosofía frente al enigma del hombre, Eunsa, Pamplona 1999, pp. 304. (F. Fernández Labastida) Juan A. García González, Teoría del conocimiento humano, Eunsa, Pamplona 1998, pp. 289. (A. Ducay) Michele Marsonet (a cura di), Donne e filosofia, Erga, Genova 2001, pp. 314. (M.T. Russo) Sabino Palumbieri, L’uomo, questa meraviglia. Antropologia filosofica I. Trattato sulla costituzione antropologica, Urbaniana University Press, Roma 1999, pp. 414. (F. Russo) John F. Wippel, The Metaphysical Thought of Thomas Aquinas. From Finite Being to Uncreated Being, Monographs of the Society for Medieval and Renaissance Philosophy no. 1, The Catholic University of America Press, Washington, D.C., 2000, pp. xxvii + 630. (S.L. Brock)